Climate Village Research Mapping Using Bibliometric Analysis - Ana Hardiana; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2026)
The climate village program is one of the national programs to increase community participation in climate change adaptation. This program is held to prepare communities that are swiftly responsive to current climate change. This study offers a knowledge map of the Climate Village Program drawing from a literature review from 2000 to 2024, which provides an overview of bibliometric analysis approaches, including analysis of time, journals, citations, countries, and institutions. Literature surveys show the direction of research contribution rates has been on an upward trend in recent years. Journal analysis shows that works on climate village programs have not been widely conducted. Hence, a potential for wider opportunities for researchers. The Climate Village Program offers several benefits in tackling climate change and promoting sustainable development. This study suggests collaboration supported by various studies and research.